Men and Miscarriage: A Systematic Review and Thematic Synthesis. (January 2020) - Williams, Helen M.; Topping, Annie; Coomarasamy, Arri; Jones, Laura L.
Miscarriage is common, affecting one in five pregnancies, but the psychosocial effects often go unrecognized and unsupported. The effects on men may be subject to unintentional neglect by health care practitioners, who typically focus on biological symptoms, confined to women. Therefore, we set out to systematically review the evidence of lived experiences of male partners in high-income countries. Our search and thematic synthesis of the relevant literature identified 27 manuscripts reporting 22 studies with qualitative methods. The studies collected data from 231 male participants, and revealed the powerful effect of identities assumed and performed by men or constructed for them in the context of miscarriage. We identified perceptions of female precedence, uncertain transition to parenthood, gendered coping responses, and ambiguous relations with health care practitioners. Men were often cast into roles that seemed secondary to others, with limited opportunities to articulate and address any emotions and uncertainties engendered by loss.